2016
DOI: 10.1093/nar/gkw1264
|View full text |Cite
|
Sign up to set email alerts
|

A specific dsRNA-binding protein complex selectively sequesters endogenous inverted-repeat siRNA precursors and inhibits their processing

Abstract: In plants, several dsRNA-binding proteins (DRBs) have been shown to play important roles in various RNA silencing pathways, mostly by promoting the efficiency and/or accuracy of Dicer-like proteins (DCL)-mediated small RNA production. Among the DRBs encoded by the Arabidopsis genome, we recently identified DRB7.2 whose function in RNA silencing was unknown. Here, we show that DRB7.2 is specifically involved in siRNA production from endogenous inverted-repeat (endoIR) loci. This function requires its interactin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 82 publications
3
41
0
Order By: Relevance
“…This was characterized by a global increase in the total amount of endoIR-siRNAs produced and a clear change in their accumulation pattern with, chiefly, a strong increase in the accumulation of DCL3-dependent 24nt small RNAs from these endogenous IRs loci, compared with wild-type plants. 31 Interestingly, a similar effect on endoIR-siRNA accumulation was previously reported in drb4 mutant plants, 33 suggesting that, somehow, both DRB4 and DRB7.2 negatively regulate the processing of these endogenous IR transcripts by the siRNAgenerating DCLs. Incidentally, bimolecular fluorescence complementation (BiFC), co-immunoprecipitation (co-IP) and RNA immunoprecipitation (RIP) experiments revealed that these 2 DRB proteins selectively interact with each other and that this complex specifically binds endoIR-siRNA precursors.…”
supporting
confidence: 66%
See 3 more Smart Citations
“…This was characterized by a global increase in the total amount of endoIR-siRNAs produced and a clear change in their accumulation pattern with, chiefly, a strong increase in the accumulation of DCL3-dependent 24nt small RNAs from these endogenous IRs loci, compared with wild-type plants. 31 Interestingly, a similar effect on endoIR-siRNA accumulation was previously reported in drb4 mutant plants, 33 suggesting that, somehow, both DRB4 and DRB7.2 negatively regulate the processing of these endogenous IR transcripts by the siRNAgenerating DCLs. Incidentally, bimolecular fluorescence complementation (BiFC), co-immunoprecipitation (co-IP) and RNA immunoprecipitation (RIP) experiments revealed that these 2 DRB proteins selectively interact with each other and that this complex specifically binds endoIR-siRNA precursors.…”
supporting
confidence: 66%
“…Accordingly, overexpression of DRB7.2 triggered a specific decrease of endoIR-siRNA accumulation, without any effect on the other classes of small RNAs. 31 The observation that, in single drb7.2 or drb4 mutant backgrounds, accumulation of DCL3-dependent 24nt endoIR-siR-NAs was the most strongly increased suggested that this complex acts primarily as a repressor of DCL3 processing on IR substrates ( Fig. 1 and ref.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…DRB4 has been shown to be both a co-factor of DCL4 in small RNA biogenesis and an inhibitor of DCL3 in endogenous inverted-repeat RNA processing in A. thaliana [39, 40]. More relevantly here, DRB4 is involved in the defense against RNA viruses [41, 42].…”
Section: Resultsmentioning
confidence: 99%